Carcinocythemia: A Rare Entity Becoming More Common? A 3-Year, Single-Institution Series of Seven Cases and Literature Review. (21st September 2018) - Ronen, Shira; Kroft, Steven; Olteanu, Horatiu; Hosking, Paul; Harrington, Alexandra
Abstract: Objectives: Carcinocythemia is a rare phenomenon defined as morphologically identifiable, circulating tumor cells (CTCs) in the peripheral blood. The presence of CTCs can cause diagnostic challenges for pathologists interpreting peripheral blood smears, as these atypical cells can in some instances overlap morphologically and even immunophenotypically with myeloblasts and lead to a mistaken diagnosis of acute leukemia. Methods: A retrospective study was conducted of all confirmed carcinocythemia cases over a 3-year period at our institution. Carcinocythemia was defined as morphologically identifiable CTCs in the blood. Blood smears from seven carcinocythemia cases were identified and reviewed. Associated clinicopathologic findings were described and compared to the literature. When available, bone marrows were also examined. Results: We present seven patients with CTCs in five females and two males with a median age of 57 years and compare them with 26 case reports in the literature (19 females and 10 males, median age of 57 years). The primary neoplasms in our cohort were carcinomas of breast (three cases); lung, non–small cell (two cases); prostate (one case); and one of unknown primary. CTCs were large with round nuclei, dispersed chromatin, and abundant pale, occasionally vacuolated, basophilic cytoplasm. CTCs were associated with fragmentation hemolysis (two cases), asplenic RBC changes (three cases), and myeloid antigen expression by flow cytometry (two cases) and were most commonly found at the feathered edge of the slide (six cases) as single cells or in clusters. Conclusion: This represents the largest series of carcinocythemia reported in the literature. CTCs are most common in breast carcinoma and may be associated with asplenism and fragmentation hemolysis. The identification of seven cases at one institution over a 3-year period suggests carcinocythemia may be becoming more common. Raising awareness of this entity and its associated clinicopathologic findings may help avoid diagnostic pitfalls in blood smear examinations and may guide timely clinical management.